2022
DOI: 10.1111/cge.14240
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperoxaluria: Comprehensive mutation screening of the disease causing genes and spectrum of disease‐associated pathogenic variants

Abstract: The primary hyperoxalurias are rare disorders of glyoxylate metabolism. Accurate diagnosis is essential for therapeutic and management strategies. We conducted a molecular study on patients suffering from recurrent calcium‐oxalate stones and nephrocalcinosis and screened primary hyperoxaluria causing genes in a large cohort of early‐onset cases. Disease‐associated pathogenic‐variants were defined as missense, nonsense, frameshift‐indels, and splice‐site variants with a reported minor allele frequency <1% in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Another large cohort study [ 16 ] of 247 American PH1 patients showed that the renal survival of patients at 20, 40, and 60 years of age were 76%, 43%, and 12%, respectively; moreover, it was found that although the gene profiles of mutations were partially different between African Americans and European Americans, the incidence predictions were similar. Another study of 205 patients with PH1 from South Asia [ 40 ] revealed that the morbidity of nephrocalcinosis and ESRD were similar to Chinese. While for the Syrians, whose median age of onset was 3 years, 72.5% had renal insufficiency at the initial visit and the mortality rate of PH1 was as high as 46.4%, which may be related to the local special social environment and medical level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another large cohort study [ 16 ] of 247 American PH1 patients showed that the renal survival of patients at 20, 40, and 60 years of age were 76%, 43%, and 12%, respectively; moreover, it was found that although the gene profiles of mutations were partially different between African Americans and European Americans, the incidence predictions were similar. Another study of 205 patients with PH1 from South Asia [ 40 ] revealed that the morbidity of nephrocalcinosis and ESRD were similar to Chinese. While for the Syrians, whose median age of onset was 3 years, 72.5% had renal insufficiency at the initial visit and the mortality rate of PH1 was as high as 46.4%, which may be related to the local special social environment and medical level.…”
Section: Discussionmentioning
confidence: 99%
“…149 AGXT mutant alleles are currently known in the Chinese population, c.33dupC and c.815_816insGA were the most common in the Chinese population, accounting for 12.0% and 10.1% of allele frequencies (Tables 3 and 4 ), respectively, and then c.32C > G, c.679_680del, c.215A > T. We searched the gnomAD and found two gene frequencies of the above common variations in Asian populations: c.32C > G (0.001407), c.215A > T (0.0001088). In South Asia, p.Gly350Asp, p.Leu101Pro, p.Gly190Arg, Cys173_His174delinsTrpAsn, and c.33dupC account for 61% of the mutant alleles [ 40 ], which were partially different from Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between the molecular and clinical aspects of PH1 can be exploited not only to explain or predict treatment responsiveness, but also to interpret the effects of newly-identified mutations. In the last years, a more rapid and comprehensive genetic characterization of hyperoxaluria patients has been performed, which in turn has increased the number of new mutations identified in the genes associated with the three forms of PH [ 52 54 , 55 ▪ , 56 ▪ ]. This situation has posed new challenges in the interpretation of missense variants, and has highlighted the use of functional studies to support pathogenicity assessment [ 57 ].…”
Section: Molecular Pathogenesis Of Primary Hyperoxaluria Type 1 (Ph1)mentioning
confidence: 99%
“…The ndings of Boussetta and companions revealed that the p.Gly190Arg mutation was the second most common mutation withan allele frequency, of 17.4 [14].The other most common mutations within the PH1 category identi ed in a study by Hashmi and colleagues were Gly350Asp and Gly82Glu [9]. In another mutational analysis study by Abid and colleagues, c.1049G > A; p.Gly350Asp genetic mutation was found in 22% of the patients with PH1 [11].Other mutational studies include c.1093G > T(p.Gly365Cys) mutation identi ed in a Japanese patient [15];the c.…”
Section: Mutational Analysis Of the Agxt Gene Causing Ph1 Across Globementioning
confidence: 99%